2022
DOI: 10.1111/jpc.16006
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department childhood anaphylaxis presentations in regional/remote Australia

Abstract: Aim Explore the prevalence of childhood anaphylaxis and clinical presentation of anaphylaxis in children across two regional emergency departments over a 7‐year period. Methods Retrospective audit of all children (0–18 years) presenting to emergency from 1 January 2010 to 31 December 2016 with anaphylaxis, defined by Australasian Society of Clinical Immunology and Allergy definitions and doctor diagnosis. Results Seven hundred and twenty‐four patients were identified with allergic diagnosis, 60% were diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
2
3
0
1
Order By: Relevance
“…Corticosteroids were found to be the most administered treatment in our EDs, with over half of adult and paediatric patients receiving at least one dose. This corticosteroid use is similar to other Australian ED studies, with use reported to range from 44 to 87% [ 11 16 , 19 ]. The evidence supporting the routine use of corticosteroids in anaphylaxis management remains a subject of debate, with increasing evidence of no benefit in the acute management phase or in preventing biphasic reactions [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Corticosteroids were found to be the most administered treatment in our EDs, with over half of adult and paediatric patients receiving at least one dose. This corticosteroid use is similar to other Australian ED studies, with use reported to range from 44 to 87% [ 11 16 , 19 ]. The evidence supporting the routine use of corticosteroids in anaphylaxis management remains a subject of debate, with increasing evidence of no benefit in the acute management phase or in preventing biphasic reactions [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…The identified rate of adrenaline administered to those presenting with anaphylaxis to ED in our study (57%) was within the range of 39% to 59% reported in previous studies [ 11 – 14 ]. Adrenaline is the first-line treatment for anaphylaxis and should be given without delay via the IM route [ 3 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations